Taking back control. Issue 6 (June 2016) - Lyon-Maris, Johnny
Workload, fear of litigation, ever-increasing patient demand, and the confrontation involved with refusing patient or colleague requests have led to a culture of just saying 'Yes'. This article looks at the causes of those stresses and gives practical suggestions that may help the clinician to say 'No' in a supportive way, reducing inappropriate demand and educating the patients, their carers, and other health and social care professionals to use the service correctly. In this way, primary care clinicians will start to take back control of their professional lives, resulting in better and more appropriate care for the patients, who must be involved and responsible for their own health. The author recognises this approach to be controversial but feels that 'more of the same' is not an option for primary care.